(untitled) (Aporte Santiaguino, 2020)
Corn is a cereal with high potential for grain production and is highly sensitive to water deffcit and nitrogen; these two factors are the main limitations of the corn producers of the Community of Vista Alegre in San Marcos-Ancash. In this sense, the objective of this research was to evaluate the yield of starchy maize in irrigated and rainfed situations with two levels of nitrogen. To do this, the study was carried out in Complete Random Block Design (DBCA) with a factorial arrangement of 2x2 in 3 repetitions. Irrigation was applied during the Critical Period (PC) between two weeks before and after flowering; and the doses of 150 and 300 kg/ha of N were supplied in the phenological stages ofV3 andV6. Thus, obtaining the best yield of starchy corn of 6; 036 tn/ha with irrigation and a dose of 300 kg/ha of N, followed by 4,397 tn/ha for the same dry-season dose.With the 150 kg/ha of N fertilization, the yields of 3; 285 and 2; 975 tn/ha in the irrigation and rainfed modalities did not express significant difference according to the Tukey test. The residual CV was 5; 228 % and the R2 97 %. Therefore, the interaction between irrigation in the PC and the fractional fertilization of 300 kg/ha ofNin stages V3 and V6 increases the yield of starchy corn.